“Why Don't You Act Like You Believe It?”: Competing Visions of Climate Hypocrisy - Gunster, Shane; Fleet, Darren; Paterson, Matthew; Saurette, Paul (Frontiers in Communication, 2018)
This paper interrogates how the notion of hypocrisy is invoked in relation to climate change and offers two key findings. First, it demonstrates that invocations of hypocrisy are not only deployed by conservative opponents of climate action, but is also by progressive proponents of such action. Second, this article shows that while hypocrisy discourse is used to support both anti- and pro-climate change perspectives, its nature and function fundamentally differs depending on who is using it. The article identifies four discrete types of climate hypocrisy discourse. Conservatives who reject climate change action tend to use two 'modes' of hypocrisy discourse. The first is an ‘individual lifestyle outrage’ mode that cultivates outrage about the hypocritical behaviour and lifestyle choices of climate activists to undermine the urgency and moral need for climate change action. The second, an ‘institutional cynicism’ mode, encourages a cynical fatalism about any proposed governmental action regarding climate change by suggesting that governments are necessarily climate hypocrites because of the economic and political impossibility of serious emissions reductions. In contrast, progressives use hypocrisy discourse in two different modes. The first involve an ‘institutional call to action’ mode that uses charges of hypocrisy to attack government inaction on climate change and demand that effective action be taken in line with their public commitment to climate action. Secondly, they also employ a ‘reflexive’ mode in which explorations of the ubiquity of climate change hypocrisy illuminate the dilemmas that virtually all responses to climate change necessarily grapple with in our current context. Overall, the article seeks to contribute to our understanding of climate change communications by (i) showing that hypocrisy discourse is not simply a sensationalist PR strategy of conservatives but is rather a broad, significant and multi-faceted form of climate change discourse; and (ii) suggesting that certain modes of hypocrisy discourse might not only represent genuine attempts to make sense of some of the fundamental tensions of climate change politics but also help us understand the challenge that the ‘entanglement’ of personal agency/choice within broader political structures presents, and thus heighten positive affective commitments to climate change action.